Verificação da performance de modelos APARCH assimétricos aplicados a dados financeiros - Gasparini, Daniela Caetano de Souza (2013)
The volatility of financial assets changes over time, indicating the specification of regime change in volatility models. Furthermore, the presence of asymmetry in the returns of the financial market has been recognized in the financial literature of recent decades. In this paper, we present some heteroscedastic models with regime change, considering that the error component of these models follows Skew Laplace distribution, as well as the process of estimating its parameters via maximum likelihood and Bayesian methods.